Association of vitamin D with HIV infected individuals, TB infected individuals, and HIV-TB co-infected individuals: a systematic review and meta-analysis - Xie, Kaidi; Zhang, Yang; Zhang, Mei; Wu, Hao; Zheng, Luyao; Ji, Jiahao; Li, Zhen; Wang, Wen; Zhang, Tong (Frontiers in Public Health, 2024)
Background: Vitamin D deficiency (VDD) is a worldwide disease. VDD is also associated with an increased risk of HIV-related comorbidities and mortality, and patients have a tendency to develop active tuberculosis compared to those with latent tuberculosis infection. Vitamin D supplementation may modulate HIV replication, improve TB inflammation and reduce progression of HIV-TB co-infection.We meta-analyzed individual participant data from cohort studies, crosssectional study, and RCTs of vitamin D in HIV group, TB group, and HIV-TB group.The primary outcomes were differences in vitamin D level and VDD prevalence between three groups, The secondary outcomes were CD4 count, HIV viral load, time to sputum smear conversion, time to culture conversion, relapse, morality, and TB score.Results: For vitamin D levels, the overall mean difference (MD) between HIV group and TB group was -0.21 (95% CI, -20.80 to 20.38; P = 0.9, I 2 = 84%), HIV group and HIV-TB group was 0.87 (95% CI, -11.45 to 13.20; P = 0.89, I 2 = 87%), and TB group and HIV-TB group was 1.17 (95% CI, -5.21 to 7.55; P = 0.72, I 2 = 85%). For vitamin D deficiency prevalence, the overall odds ratio (OR) for HIV group vs. TB group was 1.23 (95% CI, 0.46 to 3.31; P = 0.68; I 2 = 70%), HIV group vs. HIV-TB group was 1.53 (95% CI, 1.03 to 2.29; P = 0.04; I 2 = 0%), and TB group vs. HIV-TB group was 0.85 (95% CI, 0.61 to 1.20; P = 0.36; I 2 = 22%). In HIV-TB group, the overall OR for vitamin D group vs. placebo group was 0.78 (95% CI, 0.34 to 1.67; P = 0.52; I 2 = 60%).Conclusions: Our findings indicated that there were no variations in vitamin D levels between three groups. The prevalence of vitamin D deficiency was higher in the HIV-TB group than in the HIV group. Additionally, the administration of vitamin D supplements did not have obvious impact on CD4 count and viral load. Likewise, viatmin D had no effect on time to sputum smear conversion, time to culture conversion, relapse, 12-month morality, and TB score.